Aspectos-chave no processo de construção do conhecimento: considerações acerca da aprendizagem de uma criança com síndrome de Down no processo de inclusão no ensino regular - Michels, Lísia Regina Ferreira (2007)
The objective of this study was to investigate the main aspects involved in the process of construction of a child s writing with Down s Syndrome, in order to understand the indications which reveal advances in the process of appropriation of writing abilities, during regular activities, in a group in the beginning of the elementary school. The study was carried out starting from a qualitative focus of research. Besides the child with Down s Syndrome in the regular teaching as a focus, we adopted the historical and cultural theory as reference to the analysis. We analyzed the development of a child s writing in a group and in the classroom, taking into account the interactions between the children and between the teacher and the children and all support offered to the student to learn how to write. We analyzed the support network formed by social agents of the school. The data were collected through documental analysis, interviews, systematic observation of the activities in the classroom, analysis of what children wrote and analysis of bimonthly evaluations, carried out by teachers from the 1st and 2nd grades. The analysis of the data demonstrated that the students with Down s Syndrome learn the written language in the regular teaching. In order to accomplish this result, however, it is essential that the school undertakes a series of actions, among which we can highlight the following: offer resources and necessary support for it; evaluate the real level of development of the students; and plan the teaching and learning process deliberately, taking into account that it needs to be meaningful to everyone and that it happens in a shared context of interactions. For the success of the inclusive education, the school needs to invest in the continuous formation of teachers and professionals of the educational area. Without that, there is no possibility to count on the necessary technical elements to plan and establish an effective teaching for all of the students. Besides, the ones who act in the school environment need to participate and mobilize themselves, because if the teacher is the only one prepared to receive the students with deficiency, they won t progress in their learning and development. It is necessary that all those who are involved with the school have a conscious and active participation in this process